Understanding maternal food choice for preschool children across urban-rural settings in Vietnam - Cam Duong; Mica Jenkins; Euisun Pyo; Phuong Hong Nguyen; Tuyen Huynh; Hung Nguyen‐Viet; Melissa F. Young; Usha Ramakrishnan (Wiley, 2023)
Abstract Improving diet quality of preschool children is challenging in countries undergoing food environment and nutrition transition. However, few studies have sought to understand how mothers in these countries decide what and how to feed their children. This study aims to explore maternal experiences, perspectives and beliefs when making food choice decisions for preschool children in urban, peri‐urban and rural areas in northern Vietnam. Two focus group discussions and 24 in‐depth interviews were carried out and analysed using thematic analysis. The results showed that mothers across the urban-rural spectrum shared the intention to feed children safe, nutritious food for better health and weight gain while satisfying child food preferences to improve appetite and eating enjoyment. These food choice intentions were embedded within family food traditions, whereby mothers emphasised nutritious food and adopted strict feeding styles during lunch and dinner but were flexible and accommodating of child preferences during breakfast and side meals. These intentions were also embedded within the physical food environment, which provided a mix of healthy and unhealthy food through informal food retailers. Despite these intentions, mothers faced financial constraints and difficulties in managing children's refusal to chew, changes in eating mood and strong eating temperament. These findings support policies to limit the presence of unhealthy food in informal food retail and encourage meal‐specific feeding strategies to help children enjoy nutritious food, transition from soft to textured food and become more cooperative during mealtime.